Improvement of mechanical properties of aluminium matrix composites through addition of alumina by stir casting method - Nur Kholis; Sri Mulyo Bondan Respati; Evan Chahya Kurniawan (Jurnal Polimesin, 2025)
Aluminum is a material widely used in various industries. Aluminum has superior properties, one of which is corrosion resistance and good formability. However, one of the disadvantages of aluminum is that it has relatively low strength compared to other materials. Therefore, this study aims to determine the effect of adding various alumina to aluminum metal casting using the stir casting method on physical and mechanical properties. In this research, aluminum waste was used as the main matrix, and alumina powder (Al2O3) was used as reinforcing particles with weight fractions of 15%, 20%, and 25%. The material was melted at a temperature of 800 °C and a stirring speed of 500 Rpm for 5 minutes. Macro and micro observations were conducted using an optical metallography instrument. Mechanical testing included hardness testing using a Rockwell Hardness scale B instrument and tensile testing using a Universal Testing Machine. The test results showed several defects, including porosity, shrinkage, air holes, misruns, flash, and rough surfaces. Porosity and air pockets are usually caused by gas (especially hydrogen in aluminum) that is trapped during cooling due to insufficiently dry moulds or poor ventilation. The microstructure results show that Al2O3 agglomeration is highest at a 25% addition, which occurs because the stirring speed of 500 RPM is not sufficient to evenly distribute the Al2O3 particles. The highest hardness value is still found in the raw material (without reinforcement) at 73.33 HRB, while the material with the highest Al₂O₃ reinforcement at 25% addition has a hardness of 43 HRB. The highest tensile strength value was observed at the 25% alumina reinforcement parameter, with a value of 135.35 HRB, and the lowest at the 15% reinforcement addition, with a value of 128.64. The decrease in both hardness and tensile strength values compared to the raw material is attributed to alumina agglomeration.